2012
DOI: 10.1673/031.012.7701
|View full text |Cite
|
Sign up to set email alerts
|

Species Turnover and Diel Flight Activity of Species of Dung Beetles,Onthophagus, in the Tropical Lowland Forest of Peninsular Thailand

Abstract: Species turnover and temporal variation of forest insects were used to explain the ecological succession and ecological segregation between efficiently competing species. In this study, species richness, abundance, and beta-diversity of the genus Onthophagus (Coleoptera: Scarabaeidae) assemblages between 2003 and 2007 were described and the diel—flight activity was examined in the disturbed forest and the interior forest of the lowland tropical rain forest at Ton Nga Chang Wildlife Sanctuary in peninsular Thai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
7
0
2
Order By: Relevance
“…It is possible that juvenile elasmobranchs may reduce nocturnal activities to lower predation risk from larger conspecifics that actively forage during dark periods (Hammerschlag et al 2010). Individuals may also base their foraging decisions on body condition and health, as individuals in poor energetic condition may opt to assume increased predation risk in exchange for access to food resources and increases in probability of hunting success under low light conditions (Brown and Kotler 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that juvenile elasmobranchs may reduce nocturnal activities to lower predation risk from larger conspecifics that actively forage during dark periods (Hammerschlag et al 2010). Individuals may also base their foraging decisions on body condition and health, as individuals in poor energetic condition may opt to assume increased predation risk in exchange for access to food resources and increases in probability of hunting success under low light conditions (Brown and Kotler 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they reported that both habitat filtering, the co-occurrence of potential competitors along the successional gradient, based on similar environmental tolerances, and niche separation, are able to shape these temporal distributions. The significant effects of dung deposition time and exposure period and their interaction on mean guild abundance in the present study evidenced temporal separation and by inference, temporal resource partitioning, which is attributable to diel activity Boonrotpong et al 2012), interspecific aggregation patterns (Hutton and Giller 2004), size differences and changes in dung quality over time (Doube et al 1988;Lumaret and Stiernet 1991). The tunnellers preferred the dung deposited at 06:00 because it was fresh during their peak flight period in the morning.…”
Section: Discussionsupporting
confidence: 49%
“…preferences for dung of different ages reduce the potential for interspecific and interguild competition by providing multiple opportunities for a particular species in a local assemblage to acquire sufficient resource for feeding and breeding purposes, thus promoting coexistence (Montes de Oca and Halffter 1995;Palestrini et al 1995;Boonrotpong et al 2012;Sullivan et al 2016b).…”
Section: Acknowledgementsmentioning
confidence: 99%
See 2 more Smart Citations